2020
DOI: 10.3934/dcds.2020113
|View full text |Cite
|
Sign up to set email alerts
|

Spectral decomposition for rescaling expansive flows with rescaled shadowing

Abstract: In this paper, we introduce the concepts of rescaled expansiveness and the rescaled shadowing property for flows on metric spaces which are dynamical properties, and present a spectral decomposition theorem for flows. More precisely, we prove that if a flow is rescaling expansive and has the rescaled shadowing property on a locally compact metric space, then it admits the spectral decomposition. Moreover, we show that if a flow on locally compact metric space has the rescaled shadowing property then its restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Next, we recall the definition of the shadowing property for a continuous flow on a metric space X in [11]. We begin by introducing the setting in metric space.…”
Section: Basic Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we recall the definition of the shadowing property for a continuous flow on a metric space X in [11]. We begin by introducing the setting in metric space.…”
Section: Basic Definitionsmentioning
confidence: 99%
“…Regarding the dynamics of noncompact systems, a well-known difficulty is that some dynamical properties (i.e., properties that are invariant under conjugacy) on compact metric spaces may not be dynamical properties on noncompact metric spaces. For example, in [11], the authors provided an example to demonstrate that the classical shadowing property for flows on noncompact metric spaces depends on the choice of metrics; moreover, they introduced the notion of the shadowing property of continuous flows on metric spaces and showed that the extended definition is a dynamical property.…”
Section: Introductionmentioning
confidence: 99%
“…The famous spectral decomposition theorem by Smale [22] says that the nonwandering set Ω(f ) of an Axiom A diffeomorphism f on a compact smooth manifold admits the spectral decomposition, i.e., Ω(f ) can be decomposed as a disjoint union of finite basic sets B, that is, each B is a compact invariant set such that f | B is topologically transitive. There are many works that generalize the Smale's spectral decomposition theorem to more general settings (e.g., see [1,10,11,12,14,16,18,19]). Komuro [14] proved the topological version of the Smale's spectral decomposition theorem for flows on compact metric spaces.…”
Section: Proof (I) ⇒ (Ii) It Is Clear By Definitionmentioning
confidence: 99%